The method of the integral geometry for finding the distribution functions of chord length of an oval and of distance in an oval - Gečiauskas, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Гячяускас. Интегрально-геометрический метод на хождения функций распределения длинных орды овала и расстояния внутри овалаE. Gečiauskas. Integralinės geometrijos formulių taikymas ovalo stygos ilgio ir atstumo ovale pasiskirstymo funkcijoms rasti